Influence of weeds on seed development, yield components and seed quality in Okra (Abelmoschus esculentus) - Puteh, Adam; Juraimi, Abdul Shukor; Mohamad, Rosli (Universiti Putra Malaysia Press, 1995)
The presence of weeds during crop production is known to affect yield. However, changes to yield components, seed development and seed quality are not well documented. The study was conducted to determine the effect of weeds on accumulation of seed dry weight, yield components, and seed quality in okra (Abelmoschus esculentus). Treatments in the field consisted of manual weeding, no weeding or herbicide spraying. Flowers were tagged daily al flowering stage and fruits were harvested at 15, 20, 25, 30, 35 or 40 days after flowering (DAF). Changes in accumulation of seed dry weight, lOO0 seed weight, seed germination and field emergence were evaluated following all harvests. Yield components (fruits plant1 and seeds fruit1) were evaluated at 40 DAF. The presence of weeds did not affect the duration for seeds to reach maximum dry weight, but reduced lOO0 seed weight, fruits plant1 and seeds fruit1. Seeds harvested from manually weeded plats resulted in higher germination and field emergence compared with those from herbicide or no weeding plots. The presence of weeds >= 7.5% coverage) did not affect the time taken to achieve maximum germination and seed quality directly however, weeds directly affected rate of accumulation of seed d,y weight and seed size which subsequently affected germination and field emergence.